ANALISIS PENGENDALIAN DEFECT CHIPPING DIE DI MESIN DIE ATTACH PADA PT EPSON BATAM - Muhammad regi pahlawan; Fajrah, Nofriani (Computer Science and Industrial Engineering, 2022)
PT Epson Batam is a manufacturing company engaged in the production of devices, scanners, and Ink Cartridges. CISM is the department responsible for making printer scanners. One of the processes in the CISM department is the process of combining between ic or die and pcb called module using a Die Attach machine located in the FOL area. based on the QC report in 2021 there are defects in Die products which dppm per month exceeding the company's defect standard of 4.700 dppm per month. This study aims to analyze the control of defect chipping die on die attach machines. The sampling method uses probability sampling. The data analysis uses the PDCA (Plan-DO-Check-Action) method. This study also used the FMEA (Failure Mode Effect Analysis) method to find the source of the defect, continued on the OPC (Operation Process Chart) method to see whether there has been a checking process according to the SOP in the company and at the final stage of making proposed improvements to minimize the cause of the defect. The results showed that the main cause of defect chipping die was due to foreign material due to an ineffective cleaning process because it was carried out per 100,000 pcs. Based on the OPC analysis, the improvements made were to improve the cleaning schedule from 100,000 pcs to twice a day through shiftly cleaning metal collets. The defect control using the PDCA method which was carried out during March - June 2022 the CISM department succeeded in reducing defects below company standards. in the form of SOP.